Standardization of presowing seed treatment and growing media for commercial plantations of Jatropha curcas L. - Panwar, Pankaj (Indian Journal of Agroforestry, 2020)
Presowing seed treatments comprising of cold water treatment for 12 hours and 24 hours and hot water treatment for 12 hours and 24 hours along with three sowing depth 10 mm , 20 mm and 30 mm was applied in factorial design on Jatropha curcas. It was found that cold water treatment for 24 hours coupled with sowing at 30 mm depth is the best treatment for getting higher germination parameters. The germination was 90 per cent, germination value 44.40 and germination speed 19.63. Growth of the seedlings was maximum (16.50 cm) when seeds were kept in cold water for 12 hours and sown at 20 mm depth. Seven proportions of soil: fym: sand were tried to standardize the growing media for Jatropha. It was found that ratio of 1:3: 1 was the best composition of the growing media wherein germination was 76.67 per cent, germination energy 73.33, germination value 25.30 and germination speed 14.30. The growing media was not found to have significantly affected the growth of seedlings.